O jogo didático Isogames no estudo da isomeria em compostos orgânicos: indícios de aprendizagem - Barbosa, Vivian Marina (2020)
Historically, the traditional approach about contents has been criticized for its limitations regarding to the scientific knowledge. In this conception, Science is decontextualized and uncritical. Therefore, the teaching and learning contribute just a little to keep the interest and motivation in students. In this sense, this research aimed to identify the evidence of learning about isomerism in organic compounds, based on the execution of the educational game called ISOGAMES, based on problem solving and interdisciplinarity. The interest in the study of the theme arose from the analysis of my own practice, because, several times, the students had difficulty understanding concepts related to isomerism. Thus, this research was guided by the following question: Which evidences of learning, about isomerism in organic compounds, can be identified, through the execution of the educational game ISOGAMES, based on problem solving and interdisciplinarity? To get to this, the qualitative research involved the participation of forty sophomore high students of the full time Chemistry course, in one of the Technical Schools (ETECs) in the state´s countryside of São Paulo. The game itself was used for obtaining and analyzing the datas themselves; it was used Concept Maps (MCs) to the themes like adrenaline, aspartame, trans fat and vitamin C; the speeches of the involved ones and the answers to the problem questions. To identify the evidence of learning were analyzed the MCs built by the participants and, using the same resource were created MCs for each of the themes. It was indentified three categories, namely: development of criticality; disciplinary conceptual understanding (isomerism; enantiomers) and, finally, construction of interdisciplinary and contextual meanings about isomerism in organic compounds. The results indicated that the educational game ISOGAMES revealed contribution and potential for learning concepts about isomerism in organic compounds, since it was conceived from an interdisciplinary and investigative perspective. As an educational product resulting from this Dissertation, this game reflects the relationship between theory and practice and the breaking of disciplinary boundaries.